Equine thoracic wall trauma and management of pneumothorax: report of a clinical case attended under field conditions - Estrada M, Juan (2016)
Various causes of accidental trauma affecting the equinethoraxic wall and the pathophisiology of pneumothorax are mentioned.Diagnosis techniques, as well as medical and surgical management of the clinical case on a standing horse under field conditions are discussed. Two options used to depressurize the pleural cavity are explained. The paper also mentions the advantages of handling the case under local anesthetic techniques versus general anesthesia. All the procedures were performed at a farm located in the canton of Coronado, Costa Rica.